Shree Clinical Laboratory Management Application: Enhancing Workflow and Data Management Efficiency - Prashant, Bhandare; Baburao, Shinde Sourabh; Mahesh, Mali Mayur; Mahadev, Dubal Rohit; Bibhishan, Gardade Rohan (International Journal of Computer Sciences and Engineering, 2024)
The goal of the Clinical Laboratory Management Application is to improve the accuracy and efficiency of laboratory work in healthcare environments. Every clinical laboratory needs to maintain test records, and generating reports in the correct format can be quite complex. Additionally, managing the financial activities associated with patient tests poses challenges for lab technicians. This application addresses these issues, offering a user-friendly solution that simplifies record-keeping and report generation. This application will aim at creating advancement in manual keeping of clinical data records. This application streamlines processes such as sample tracking, result reporting, inventory management, and compliance with regulatory standards. Clinical Laboratory Management`s features, which include user-friendly interfaces, automated workflows, and strong security measures, not only support quality improvement initiatives but also increase operational efficiency, which ultimately improves patient outcomes and makes the healthcare delivery system more efficient.